KEBIJAKAN TINDAK PIDANA PADA KEJAHATAN NARKOTIKA DI INDONESIA - Puput Dedi Kurniawan; Muhamad Hasan Sebyar (JOURNAL OF LAW AND NATION, 2023)
Law No.22 of 1997 concerning narcotics states that narcotics are subtances or drugs derived from plants or non-plants,either synthetic or semi-synthetic,which can cause a decrease or change in consciousness,loss of taste,recudeor eliminate pain,and can cause dependence.According to the ministry of health of the republic of Indonesia,drugs are an abbreviation for narcotics,psychotropics and addictive subtances.All of these terms,whether narcoticsor drug use,refer toa group of subtances that generally pose a risk of addiction for their users.As time goes by,someone who was initially unfamiliar with narcotics turn into an addict who finds it difficult to get rid of his addiction.Rehabilitation of narcotics addicts is also a form of social protection that integrates narcotics ddicts into social order so that they no longer abuse narcotics.Narcotics crime is a very complex problem that requires comprehensive mitigation efforts involving multi-disciplinary ,multi-sector coorperation and active community participation which is carried out consistently ,consistently and consistently.The purpose of this research is to find out penal and non-penal policies in dealing with narcotics crimes at this time and the problem discussed is what the criminal policies for narcotics crime are in the country Indonesia.Penal policy is to overcome crimes committed by implementing criminal law in society,while non-policing penal means dealing with crime without using criminal law namely by influencing people’s views about crime through mass media and countermeasures without punishment